Increased HLA-DR expression and cortical demyelination in MS links with HLA-DR15. Issue 2 (March 2020) - Enz, Lukas Simon; Zeis, Thomas; Schmid, Daniela; Geier, Florian; van der Meer, Franziska; Steiner, Guido; Certa, Ulrich; Binder, Thomas Martin Christian; Stadelmann, Christine; Martin, Roland; Schaeren-Wiemers, Nicole
Abstract : Objective: To investigate molecular changes in multiple sclerosis (MS) normal-appearing cortical gray matter (NAGM). Methods: We performed a whole-genome gene expression microarray analysis of human brain autopsy tissues from 64 MS NAGM samples and 42 control gray matter samples. We further examined our cases by HLA genotyping and performed immunohistochemical and immunofluorescent analysis of all human brain tissues. Results: HLA-DRB1 is the transcript with highest expression in MS NAGM with a bimodal distribution among the examined cases. Genotyping revealed that every case with the MS-associated HLA-DR15 haplotype also shows high HLA-DRB1 expression and also of the tightly linked HLA-DRB5 allele. Quantitative immunohistochemical analysis confirmed the higher expression of HLA-DRB1 in HLA-DRB1*15:01 cases at the protein level. Analysis of gray matter lesion size revealed a significant increase of cortical lesion size in cases with high HLA-DRB1 expression. Conclusions: Our data indicate that increased HLA-DRB1 and -DRB5 expression in the brain of patients with MS may be an important factor in how the HLA-DR15 haplotype contributes to MS pathomechanisms in the target organ.